Advances in the Prediction and Risk Assessment of Lung Cancer-Associated Venous Thromboembolism - Di W (Dove Medical Press, 2021)
Wenjuan Di, Haotian Xu, Ting Xue, Chunhua Ling Department of Respiratory and Critical Care Medicine, The First Hospital Affiliated of Soochow University, Suzhou City, Jiangsu Province, People’s Republic of ChinaCorrespondence: Chunhua LingDepartment of Respiratory and Critical Care Medicine, The First Hospital Affiliated of Soochow University, No. 188, Shizi Street, Gusu District, Suzhou City, Jiangsu Province, People’s Republic of ChinaTel +86-18351071532Email linchunhua88@hotmail.comAbstract: According to the most recent data from the National Cancer Center, venous thromboembolism (VTE) has unsurprisingly become one of the most common complications in lung cancer. VTE not only interferes with the equilibrium of the clotting system but it also affects tumor progression and prognosis. For the identification of high-risk patients, many clinical risk assessment models have been developed and validated based on the risk factors found in previous studies. In this review, we will summarize advances in prediction and risk assessment of VTE, with a focus on early diagnosis and therapy, reduction of mortality, and the burden of medical costs in lung cancer patients.Keywords: lung cancer, venous thromboembolism, risk factor, risk assessment model, anticoagulation